Principles and practice of intraperitoneal chemotherapy for ovarian cancer. Issue 1 (1st January 2007) - Fujiwara, K.; Armstrong, D.; Morgan, M.; Markman, M.
Abstract : Intraperitoneal (IP) chemotherapy has been studied for years to improve the survival of patients with ovarian cancer. Recently, the result of Gynecologic Oncology Group 172 trial comparing IP versus intravenous administration of cisplatin-based chemotherapy was published, demonstrating the improvement of survival benefit in favor of the IP arm. This trial is the third trial that showed a survival benefit on IP chemotherapy. The National Cancer Institute (NCI) and Gynecologic Oncology Group have done a meta-analysis on the results of these three US trials and other phase III trials of IP versus intravenous chemotherapy, and significant improvement of survival was shown with IP therapy. Based on this meta-analysis, NCI has released a clinical announcement encouraging the gynecological oncology community to consider IP chemotherapy as the standard treatment for optimally debulked advanced ovarian cancer patients. However, there still are controversial issues regarding the use of IP chemotherapy. It is important to understand how IP chemotherapy works to solve those issues in the future. In this review article, we discuss the principles and clinical aspects of IP chemotherapy and also discuss the current problems and future perspectives in IP chemotherapy